Application of Bioelectrical Impedance Analysis to Detect Broiler Breast Filets Affected With Woody Breast Myopathy - Morey, Amit; Smith, Avery E.; Garner, Laura Jewell; Cox, Marlin K. (Frontiers in Physiology, 2020)
Woody breast (WB) myopathy in modern broilers is causing major meat quality issues and consumer complaints. The poultry industry is sorting out WB breast fillets through the inconsistent manual hand-palpation method. Bioelectrical impedance analysis (BIA) method was evaluated as a rapid and objective woody breast detection method. Freshly deboned broiler breast fillets (15 fillets x 2 categories x 3 trials) were sorted (hand-palpation) into severe woody (SW) and normal (N) categories were analyzed for BIA values, cook loss, texture (BMORS) method. SW fillets had significantly (P<0.05) higher resistance and reactance compared to N indicating BIA can be used to detect WB fillets. In another experiment, we determined the ability of the BIA to differentiate between four WB severity levels using the whole fillet. Significant differences were observed in resistance and reactance of normal and other WB categories however, there were no significant differences among mild, moderate and severe WB categories. Segmental BIA of those fillets indicated that BIA can be used to separate crania, medial and caudal region of the breast fillet based on the presence of woody breast myopathy. Accidental discovery of spaghetti breast in the samples demonstrated the significance of compounding different factors in analyzing woody breast meat using BIA.